Cultural relationship between Afghanistan and Iran during the reign of Amir Amanullah Khan - Mohammad Bashir Elham; Shirali Samimi (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2023)
This study aims to examine the historical context, dynamics, and implications of the political and cultural relations between Afghanistan and Iran during the reign of Amanullah Khan (1919-1929 AD). The method employed involves analyzing historical records and narratives to understand the initial cordiality between Amanullah Khan and Reza Shah, their visits to each other's countries, and the subsequent deterioration of political relations. Despite external influences from global powers that sought to hinder the expansion of political, economic, and cultural ties between the two nations, the shared history and interests of Afghanistan and Iran fostered a strong cultural relationship. This study finds that cultural relations served as a reliable foundation for enhancing overall bilateral relations, often compensating for fluctuations in political interactions. The implications of this research highlight the significance of cultural relations as a means to strengthen and diversify ties between neighboring countries, suggesting that a focus on cultural exchange can yield positive outcomes even in the absence of strong political alliances.